A Scene in the Forty Thievs. Performing at the Theatre Royal. - Williams ? (Walker, 1806)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Theatre Royal; Great Britain -- Politics and government -- 1800-1837